Non-steady wear of a two-layer coating taking into account frictional heating - Zelentsov, Vladimir Borisovich; Mitrin, Boris Igorevich; Kuznetsova, Tat’yana Anatol’yevna; Lapitskaya, Vasilina Aleksandrovna (Computational Continuum Mechanics, 2020)
The application of two-layer coatings is one of the most widely used ways to increase the performance capacity of heavily loaded frictional joints. Designing of two-layer coatings for dry sliding friction surfaces and the estimation of their efficiency require the development of mathematical models of sliding contact allowing for wear and frictional heating. To achieve this goal, we consider a transient quasi-static contact problem of uncoupled thermoelasticity of a rigid punch sliding with a constant velocity over the surface of a two-layer elastic coating bonded on its bottom face to a rigid half-plane (the substrate). During sliding, the punch penetrates the two-layer coating perpendicular to its surface. The friction between the punch and the coating surface is modelled taking into account the Coulomb friction. The heat flow generated by friction is directed into the depth of coating. The frictional sliding contact leads to wear of the two-layer coating. A solution to this problem is developed using the Laplace integral transform. As a result, the basic characteristics of each layer (displacements, stresses) are presented in the form of contour integrals of the meromorphic functions. The analysis of the properties of the integrand poles in the complex plane of integration makes it possible to evaluate contour integrals. The influence of the problem parameters on the main characteristics of the sliding contact (temperature, wear, stress) is investigated. As an example, the problem of wear of a two-layer titanium nitride/titanium (TiN/Ti) coating is considered. The numerical results show that by adjusting the coating layer thickness one can improve the wear resistance and reduce the contact temperature.
Keywords: wear; sliding contact; two-layer coating; frictional heating; quasistatic; mathematical modelling